ANALISIS KONSTRIBUSI PERUSAHAAN TERHADAP EKONOMI MASYARAKAT - Febriyanto - (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2015)
Corporate social responsibility is becoming a common topic that is often discussed.Company as part of a community always wanted a place where environmental sustainabilityundertaking. Therefore, the company can realize as much as possible the presence of an operationalresponsibility for the actions committed against society and the environment.Contributions company is activity in the company in accordance with its function is as a toolto carry out planning and control. Economic Community contribution to the Queen of East LampungDistrict of Labuan is in addition to having a positive contribution, also have a negative effect on thesurrounding community. Contribution of the Vendor in the economy only to the extent thatemployment is directly will increase the income/economic community around the company, but withthe increase of people's income is, they are not motivated to open their own business (standalonenot public) .Systematics that can be done in the implementation of the company's contribution, amongothers, by identifying the problem first, then find solutions and solving the problem, take actionagainst problem solving, monitoring and evaluation of the last. Corporate social responsibility has avery important function in developing corporate social environment so that the developmentcommunity will be in line with the development of the company.